Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Guru Dengan Komitmen Organisasi Sebagai Variabel Intervening Di SMA 1 Pancung Soal - Ichsanul Khairi; Dori Mitra Candana; Chintya Ones Charli (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of transformational leadership and work motivation on teacher performance with organizational commitment as an intervening variable at SMA Negeri 1 Pancung Soal. This research uses a quantitative approach with a survey method through questionnaire distribution to all teachers. The sampling technique applied is saturated sampling, where the entire population is used as research respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (PLS) with SmartPLS 3.0 software, including outer model testing, inner model testing, and hypothesis testing. The results show that transformational leadership has a significant effect on organizational commitment and teacher performance. Work motivation has a significant effect on organizational commitment but does not have a significant direct effect on teacher performance. Organizational commitment significantly affects teacher performance. Furthermore, organizational commitment mediates the effect of transformational leadership and work motivation on teacher performance. These findings indicate that improving teacher performance is influenced not only by leadership and motivation directly but also through strengthening organizational commitment.